DOES ISLAMIC SOCIAL CAPITAL ENHANCE SMEs SUSTAINABLE PERFORMANCE? - Yusfiarto, Rizaldi; Pambekti, Galuh Tri; Setiawan, Ananda; Khoirunnisa, Annes Nisrina; Nugraha, Septy Setia (Journal of Islamic Monetary Economics and Finance, 2022)
The study examines the roles of Islamic social capital and firm innovativeness in maintaining sustainable performance of SMEs in Indonesia. Compiling data from 186 respondents and using the partial least squares structural equation modeling approach (SEM-PLS), the study documents the importance of Islamic social capital for many aspects of businesses. The Islamic social capital not only supports business activities but also strengthens business networks, which in turn boosting firms’ innovation its performance.AcknowledgmentThe authors would like to thank Bank Indonesia.